Development of a Mathematics Module Based on HOTS Questions on Social Arithmetic Material - Lubis , Mara Samin; Br Ginting, Siti Salamah (Jurnal Riset Pendidikan Matematika, 2025)
This research was development research which produced a product in the form of a mathematics module based on HOTS (Higher Order Thinking Skills) questions on social arithmetic material. This research aimed to develop a mathematics module based on HOTS questions on social arithmetic material and to determine the validity, practicality and effectiveness of the module developed. The development model used is the Thiagarajan 4-D model. This module was said to be very valid from the material and media aspects, as can be seen from the results of the average total score for the two validators being 88% and 90% with very valid criteria for materi and media experts. This module was said to be practical, as can be seen from the average score of student responses to the module of 82.78%, which has very practical criteria. This module was said to be effective, as seen from the post-test results, namely that there were 84.62% who had achieved completeness, namely the score obtained was above the KKM (Minimum Completeness Criteria) score. So it can be concluded that the HOTS question-based mathematics module on social arithmetic material was classified as valid, practical and effective for use as student independent teaching material.